A Study on the Application of Restorative Justice in the Settlement of Defamation Crimes Based on Customary Law, Especially the Toba and Karo Batak Customs - Kartina Pakpahan; Desi Leolinta Br. Karo; Timothy Gilbert Sagala (Master of Law Program, Ekasakti University, 2026)
This study examines the application of the restorative justice approach in the Batak customary law system as an alternative mechanism in restoring justice in criminal cases. The focus of the study is to identify the relevance of Batak indigenous values, including the Toba and Karo Batak, to the principles of restorative justice and to identify various challenges and opportunities in the process of their integration into the national legal system. Studies show that the concept of restorative justice has fundamentally taken root for the Batak people, because values such as relationship restoration, deliberation, and peace have long been practiced through the principles of Dalihan Na Tolu and the Pupur Sage tradition. Dispute resolution in indigenous peoples is carried out through a deliberative forum involving indigenous leaders, parties to the dispute, and family elements, with the aim of creating a balanced consensus and reconciling disturbed harmonization. The customary sanctions applied are generally corrective and educational, for example, apologies or accountability, in line with the restorative justice pillar that prioritizes the healing of the victim as well as the moral accountability of the perpetrator. Nevertheless, the implementation of customary norms still encounters juridical obstacles, especially regarding the lack of legitimacy in the national legal framework and the procedural discrepancy of positive law. The opportunity to integrate customary law into a formal system is actually wide open thanks to the latest regulations from the Prosecutor's Office and the Police regarding restorative justice. The conclusion of this research shows that strengthening the authority of indigenous leaders supported by collaboration with law enforcement officials can transform Toba and Karo customary law into an efficient conflict resolution mechanism that is in harmony with the state legal order.